A case-study comparison of analysing soccer performance using the Bloomfield movement classification and a new system (Robinson Movement Classification) - Robinson, G.; O'Donoghue, P. (World Congress of Performance Analysis of Sport VIII, 2008)
Bloomfield et al. (2004) suggested that the truly intermittent nature and diversity of actions within team sports can be better captured by a larger category system and by estimating the intensities involved. Although there are a significant number of sources of variation including, individual performance capacity, position and importance of the competition, by having numerous observations of players a representative profile can be established of the physical demands of different positions. However, in using an intricate analysis tool such as the BMC, it becomes increasingly difficult to identify patterns within data sets. The present investigation addressed this issue by drawing comparisons between the BMC and the RMC. Direct comparison of the 2 approaches, using the same video footage for analysis, highlighted several differences. The main findings highlighted that the BMC approach regards turns as instantaneous events. However, turning movements are the fundamental elements which comprise the RMC approach. The turns in this approach are clearly defined and comprise a durational aspect as they encompass movements pre- and post turn. Bloomfield et al. (2007) suggested that agility requirements of soccer can be enlightened by knowledge of the volume and type of turning movements performed during competitive matches. Hence, the evolution of the RMC approach could prove vital to the development of agility training and also to the understanding of movements associated with injury risk. Bloomfield et al. (2007) suggested that the nature of movements that turns are performed within or between can be analysed by exploring temporal relationships between movements performed pre and post turn. However, by adopting the RMC approach, movement patterns are immediately, easily recognizable. Adopting this approach enables immediate results to be acquired in the absence of certain temporal pattern analyses which are both time-consuming and on occasion fail to deduce desirable outcomes (Bloomfield et al., 2005). Concurrently, results acquired using the BMC approach reflected an overestimation of the occurrence of movement instances (933 compared to 447 using the RMC approach). The analysis detailed movements as singular entries and failed to enable the analyst to recognise certain patterns within the movement instances that are `hinged` by turns or path changes. These results were supported by those of Bloomfield et al. (2007) who found that when modifiers are considered in isolation, the frequencies and mean durations reported show that some instances of locomotive movements are composed of different segments where locomotive movement is performed in different directions or at varying intensity (Bloomfield et al., 2007). When considering temporal analysis especially of high intensity bursts of activity, this aspect of performance is indeed of high importance (Spencer et al., 2005).